Method for diagnosing data errors of a computer system functioning in the system of residual classes - Koshman, Serhii; Krasnobayev, Victor; Nikolsky, Serhii (Національний технічний університет "Харківський політехнічний інститут", 2021)
The subject of the article is the development of a method for diagnosing data errors of a computer system functioning in the residue number system (RNS). This method is based on the tabular principle of data diagnostics operation implementation. The purpose of the article is to reduce the time of performing the operation of diagnosing the data of a computer system that functions in the RNS in the dynamics of the computational process. Tasks: to analyze the possible application of RNS as a number system in computer data processing systems; to investigate existing methods of data diagnostics and identify possible shortcomings in data diagnostics in the dynamics of the computational process with the introduction of minimal information redundancy; to develop a method for diagnosing the data presented in the RNS, which is based on the tabular principle of the implementation of the diagnostic operation. Research methods: methods of analysis and synthesis of computer systems, number theory, coding theory in RNS. The following results were obtained. The work shows that the data diagnostics is carried out after the control operation has been performed. To carry out the operation of diagnosing data in the RNS, when one-time errors occur, methods for determining an alternative set (AS) of numbers are used. In this case, the main disadvantage of the considered methods is the considerable time required to determine the AS. To reduce the time for determining the AC numbers in the work, the method for diagnosing data in the RNS has been improved. Improvement of the method involves the compilation of a table (the first stage) of correspondence to each correct number of a possible set of incorrect numbers when one-time errors occur in the data. Based on the analysis of the contents of the table of the first stage, a table (of the second stage) is drawn up of the correspondence of each incorrect number to the possible values of the correct numbers. Conclusions. The use of the improved method increases the efficiency of diagnostics of the data presented in the RNS by reducing the time for determining the AC numbers. This is achieved by quickly fetching pre-calculated AC table values.

Предметом статті є розробка методу діагностики помилок даних комп'ютерної системи функціонує у системі залишкових класів (СЗК). Даний метод ґрунтується на табличному принципі реалізації операції діагностики даних. Метою статті є зменшення часу виконання операції діагностики даних комп'ютерної системи, яка функціонує у СЗК в динаміці обчислювального процесу. Задачі: провести аналіз можливого застосування СЗК як системи числення у комп'ютерних системах обробки даних; дослідити існуючі методи діагностики даних і виявити можливі недоліки при діагностиці даних у динаміці обчислювального процесу при введенні мінімальної інформаційної надмірності; розробити метод діагностики даних представлених у СЗК, який заснований на табличному принципі реалізації операції діагностики даних. Методи дослідження: методи аналізу і синтезу комп'ютерних систем, теорія чисел, теорія кодування у СЗК. Отримані наступні результати. В роботі показано, що діагностика даних проводиться після виконання операції контролю. Для проведення операції діагностики даних у СЗК, при виникненні однократних помилок, використовуються методи визначення альтернативної сукупності (АС) чисел. При цьому основним недоліком розглянутих методів є значний час, необхідний для визначення АС. Для зменшення часу визначення АС чисел в роботі удосконалено метод діагностики даних у СЗК. Удосконалення методу передбачає складання таблиці (першого ступеня) відповідності кожному правильну числу можливій сукупності неправильних чисел при виникненні у даних однократних помилок. На підставі аналізу вмісту таблиці першого ступеня, складається таблиця (другого ступеня) відповідності кожного неправильного числа можливим значенням правильних чисел. Висновки. Використання вдосконаленого методу підвищує ефективність діагностики даних, які представлені у СЗК, за рахунок зменшення часу визначення АС чисел. Це досягається за рахунок швидкої вибірки попередньо розрахованих табличних значень АС чисел.
Метод діагностики помилок даних комп'ютерної системи, що функціонує у системі залишкових класів
Keywords: number system; data diagnostics; table implementation; система числення; діагностика даних; таблична реалізація